Digital Quality Management in Higher Education - A. O. Budarina; K. L. Polupan (Moscow Polytechnic University, 2019)
The study first examines the concept of digital quality management in higher education, and is aimed at featuring the theoretical justification and practical implementation of digital quality management of education at the university level. A fundamental difference between digital quality management and traditional quality management is shown. The authors present and describe the features and advantages of the developed technology of interactive intellectual environment, which is the basis of digital management. The functionality of quality management in higher education is revealed on the basis of a participative synergistic approach. The practical significance of the study lies in the introduction of an interactive intellectual environment into the higher education system, which enables the effective digital management of the quality of education. The main results comprise building an individual learning trajectory, depending on the diagnosed abilities and intelligence of each student, as well as conditioning students' research competencies as a means of improving the quality of higher education. Further development of this topic is seen in the study of the cultural aspects of interaction in the educational process, implemented in digital management.